Possible Harmful Effects of Smoking Hookah on Sperm DNA Fragmentation Index and Protamine Genes Expression in Normozoospermic Men - Maryam Tofighi Niaki; Mohammad Hasan Sheikhha; Mohammad Ali Khalili; Farzaneh Fesahat; Ali Nabi; Mahin Izadi; Saeed Ghasemi Esmailabad; Ali Reza Talebi (SAGE Publishing, 2023)
Objectives: In recent years, smoking water pipes or hookah has increased among adolescents in most countries. Although there is evidence in support of the negative effects of this type of smoking on human health, such as the increased risk of lung disease, little is known about the potential effects of hookah smoking on the male reproductive system, especially on the molecular aspects of sperm. Patients and methods: This cross-sectional study examined sperm DNA fragmentation index, protamine 1 and 2 (PRM1 and PRM2 ) genes expression, and oxidant status in normozoospermic hookah smokers in comparison with non-smoker controls. Results: Our results showed significantly higher rates of DNA fragmentation, protamine deficiency, and abnormal chromatin condensation in the spermatozoa of hookah smokers ( P  < .0001). Also, protamine gene expression showed a remarkable decrease in hookah smokers (1.55 ± 2.54 and 0.33 ± 0.54) compared to the controls (3.49 ± 5.41 and 1.22 ± 1.96), although the reduction was not statistically significant ( P  = .155 and P  = .066, respectively). Moreover, a significantly higher level of semen MDA was observed in the case group compared to the controls (0.39 ± 1.04 vs 0.15 ± 0.21; P  = .013). Conclusion: According to our study, although hookah smoking does not have a significant effect on sperm parameters, it may have deleterious effects on DNA integrity, oxidative status, and nuclear protein levels of spermatozoa.